ผลของโปรแกรมบำบัดแบบตั้งเป้าหมายชีวิตต่อการทำหน้าที่ของผู้ป่วยโรคอารมณ์แปรปรวนสองขั้ว - พรรณ์นิภา ไชยผง (จุฬาลงกรณ์มหาวิทยาลัย, 2016)
This research is a quasi-experimental research design were used nonequivalent comparison-group design. The objectives were: 1) to compare function of patients with bipolar disorder before and after received the life goals therapy program. and 2) to compare function of patients with bipolar disorder who received the life goals therapy program and who received the usual care. The 40 samples were patients with bipolar disorder, who were the out patients of Nakornratchasima Rajanagarindra Psychiatric Hospital. They were matched pair by sex and severity of depression or mania then randomly assigned to the experimental and control groups as 20 subjects in each group. Research instruments comprised of: 1) Life goals therapy program 2) Knowledge on Bipolar disorder test 3) Montgomery Asberg Depression Rating Scale 4) Thai Mania Rating Scale 5) The Functioning Assessment Short Test. The content validity of all instruments had verified by 5 professional experts. The 5th instruments had Cronbach s Alpha reliability of .87. The t-test were used in data analysis. The conclusions of this research are as follows: 1) The functioning of patients with bipolar disorder who received a life goals therapy program was significantly better than that before (p< .05). 2) The functioning of patients with bipolar disorder who received a life goals therapy program were significantly better than those who received the usual care. (p< .05).